Diversity of fish and macrobenthos at the coastal area of Tanjung Kidurong Power Plant (TKPP), Sarawak, Malaysia - Kalimuthu, Keswarran; Hamli, Hadi; Tingang Engan, Michael; Rasidi, Julaidi; Mohammad Rabullah; Ismail, Johan; Al-Asif, Abdulla; James Gerusu, Geoffery (The Egyptian Society for the Development of Fisheries and Human Health, 2022)
The regular assessment of faunal diversity near the energy power plant has gained the interest of many researchers. The activity and the effluent discharged from the power plant have remarkably stressed the adjacent assemblage of the alpha biotic community surrounding the power plant. Hence, this study aimed to assess the alpha faunal diversity of fishes and benthos in the bordering areas of Tanjung Kidurong Combined Cycle Power Plant (TKCCP), Bintulu Sarawak. The investigation was conducted in the coastal area from 2019 to 2020. Different ecological indices such as the evenness index, Margalef richness, and Shannon-Weiner diversity index were implemented, along with the cluster analysis of other stations. A number of 141 fish individuals were recorded, containing 40 species of 19 families. In addition, 13182 individuals of benthos communities from six classes and 37 species were identified. A percentage of 78 comprised fishes, while 22% were identified as crustaceans. Among the benthos addressed, Foraminifera was the major group (74%), followed by bivalve (10%) and Scaphopoda (7%). Compared to SEB2, 3 & 4, SEB1, the nearest to the power plant, recorded the highest richness, number of species, and diversity indexes. Cluster analysis, PCA, and nMDS analysis suggested that SEB2, SEB3, SEB4 had similar biodiversity compositions. The study of benthos indicates that SEB1 possesses a distinguished value of diversity and evenness indexes. This study would provide future researchers with vital documentation to evaluate the impact of thermal discharge from the power plant on alpha biodiversity in Bintulu, Sarawak, Malaysia.